NETWORK FOR THE PROMOTION OF INTERCULTURAL EDUCATION THROUGH MUSIC (NETIEM) (International Library of African Music, 1992)
"We in South Africa face the difficulty of transforming the traditions of segregation by nurturing attitudes of tolerance, respect and understanding of our cultural diversity. By sharing information and ideas, as well as visions of the future, insights will be forthcoming and strength will be derived. The assumption on which the Network is based is that an intercultural approach to education through music will nurture positive attitudes toward the value of all musics and all people".
Keywords: African Music